Voltage stability analysis of electric power system connected with distributed gennerators. - Trinh, Trọng Chưởng (Journal of Technical Education Science, 2009)
It is very common today to find renewable energy resources connected to distribution systems. The impact of this DG on voltage distribution levels has been addressed in the literature. Distributed generation is electric power source sited close to electricity consumption places thus eliminating the unnecessary transmission and distribution costs. In addition, DG can reduce the use of fossil fuels, add versatility of source and reliability of power supply, reduce power losses and improve the distribution feeder voltage conditions. This paper presents a method to study the relationship between the active power and voltage (PU) at the Point of Common Coupling to identify the voltage stability limit. It is a foundation to build a permitted working operation region in complying with the voltage stability limit at the load bus. This method can be used in teaching to students at the Faculty of Electrical Engineering